Prevalence of Cardiovascular Diseases among Complete Denture Patients - Chaitanya Shree.P1 , V. Rakshagan2 , Subhashree.R2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Cardiovascular diseases are conditions causing blocked or narrowed blood vessels leading to chest pain,myocardial infarction or stroke. Sometimes it can be associated with dental diseases like caries, periodontaldisease leading to tooth loss. In the present study, we assessed the prevalence of cardiovascular diseasesamong Complete denture (CD) Patients. Patient records were collected by complete analysis of data of86000 patients between March 2019 to March 2020. The data on the patient’s medical history and treatmentwere extracted from the patient’s records and reviewed. Totally 421 case sheets were collected and usedfor our study. The collected data were entered in excel and transferred to SPSS for analysis by Chi squaretest. We found that 1.19% of complete denture patients were affected with cardiac problems and all theaffected patients were males. Among them, 0.71% of patients between the age group 51 to 70 years weremore commonly affected with cardiac problems. In the present study, we found that cardiac problems arestatistically not significant (p>0.05). Though the association of cardiac problem between age and gender wasfound to be statistically not significant, we found that patients (especially males) between 51-70 years weremore commonly affected by cardiac problems.